Survival Analysis of Hungarian Large White, Duroc and Pietrain Sows - Baginé Hunyadi, Ágnes; Kusza, Szilvia; Balogh, Péter (Acta Agraria Debreceniensis, 2016)
The aim of the present study was to perform lifetime performance analysis in three pig breeds; Hungarian Large White (n=295), Duroc (n=76) and Pietrain (n=91) on a commercial farm using analysis of survival sows. We took into consideration the age of sows at the time of their inclusion into breeding, their age at the time of culling, time spent in production, number of mating and parities, parity percentage, intervals between litters, number and mean of piglets born alive and born dead, number of raised piglet litters, number and mean of 21 days old piglets, the weight and mean of raised litter and raise percentage.We carried out the analysis by SPSS 22.0. Single factor analysis of variants, Kaplan-Meier analysis and Cox PH model were used. The determination of the significance of risk rates differences was done by Wald chi square test.Our results showed that the average culling age were 1056 (±33.52) days for the Hungarian Large White, 735 (±73.56) days for Duroc and 818 (±71.98) days for the Pietrain.The log rank test of the survival analysis indicated a significant difference between the three tested genotypes (χ2=16.981, P